Self-Locked Asynchronous Controller for RISC-V Architecture on FPGA - Deeg, Florian; Sattler, Sebastian (GMM-Fachberichte, 2024)
We present a new approach for designing an asynchronous control unit for a RISC-V processor using dual-rail domino logic and a self-locking mechanism. The proposed method is based on the observation that dual-rail domino logic can be mapped to look-up tables in FPGAs. This allows for the design of a self-locking asynchronous control unit that is both inherently structurally safe and efficient. First we discuss the concept of dual-rail domino logic and its advantages for asynchronous circuits. A self-locking mechanism is presented that can be used to prevent asynchronous circuits from entering erroneous states. The mechanism is based on the use of a pulse circuit that locks the input, triggers a precharge and then an evaluate phase until it acknowledges the outputs and unlocks the input. This ensures that the circuit is in a stable state before it starts the computation. Afterwards, we apply the proposed approach to the design of an asynchronous control unit for a RISC-V processor. The control unit is implemented using look-up tables and function stable circuits. The result is a control unit that is both safe and efficient.
CRIS-Team Scopus Importer:2024-09-06